일 지역 여성의 임신기와 수유기 칼슘섭취 양상 - 안숙희(Ahn Sukhee); 김진희(Kim Jinhee) (근관절건강학회지, 2011)
Purpose: The purpose of the study was to identify the amount of calcium intake during late pregnancy and breastfeeding and compare the differences in the amount of calcium by subjects' characteristics. Methods: With a descriptive survey design, 121 Korean breastfeeding women were recruited in a community setting. The list of foods and drinks with calcium extracted from the study of Song and So (2007) was used to measure the amount of calcium intake during pregnancy and lactation. The subjects' characteristics were collected to identify differences in the amount of calcium intake. Results: Mean age of the women was 31 years old. Amount of calcium intake was 568mg per day during late pregnancy and 431mg per day during breastfeeding. These amounts were quite lower than a recommended dose that adult women should consume a daily minimum of 1,000mg of calcium. Women who had higher household income and attending experience for nutritional education took more calcium during breastfeeding and late pregnancy, respectively. Conclusion: More than a half of the breast-feeding women do not consume the recommended dose of calcium. Education for proper calcium consumption during pregnancy and lactation should be an additional subject in the prenatal and breastfeeding education program for women's bone health.